Production of interferon-β by fibroblast cells on membranes prepared by extracellular matrix proteins - Higuchi, Akon (Kluwer Academic Publishers, 2002)
The fibroblast cells from normal human skin were cultured on Langmuir-Blodgett (LB) and cast membranes prepared using extracellular matrix proteins (e.g., collagen, fibronectin, laminin and vitronectin). The cell density of the fibroblast cells cultured on the cast membranes was found to be higher than that on the cast membranes made of fibronectin, vitronectin and collagen-blended membranes. This indicates that not only the primary structure of proteins but the preparation methods of the membranes, i.e., casting and LB methods, are a strong factor affecting cell growth. The concentration and production of interferon-β per unit cell were found to be higher on the LB membranes than on the cast membranes made of the same proteins except in the case of collagen. However, the cell density on the cast membranes was higher than that on the LB membranes. These results appear to result from the suppressed growth of NB1-RGB cells on the LB membranes leading to the enhanced production of interferon-β on the LB membranes. The highest production of interferon-β per unit cell was observed for the NB1-RGB cells on the collagen-blended membranes with fibronectin and vitronectin. The collagen-blended membranes appear to offer a more natural and appropriate environment for NB1-RGB cells to produce interferon-β.